INDONESIA’S DIPLOMACY AT THE UN: SUPPORTING THE DECOLONIZATION OF TUNISIA (1951-1956) - Muhamad Aditya Setiawan; Muhammad Arya Dwiki Ressa Adriani; Genta Ramadhan (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This article analyses Indonesia’s diplomacy at the United Nations (UN) in support of Tunisia’s decolonization from French colonial rule between 1951 and 1956. As a newly independent state and a recent member of the UN in the early 1950s, Indonesia strategically utilized the organization as a multilateral platform to articulate anti-colonial norms and to advocate the right to self-determination for colonized peoples. This study adopts historical methodology comprising heuristics, source criticism, interpretation, and historiographical reconstruction, drawing upon primary sources from UN archival documents and secondary sources from internationally indexed scholarly publications. The findings reveal that Indonesia acted as an active diplomatic advocate of Tunisian independence by consistently raising the issue within the UN and by forging strategic cooperation with Asian states. Indonesia’s diplomatic support for Tunisia constitutes a significant illustration of how a postcolonial state mobilised international legitimacy and multilateral pressure to challenge colonial domination. Furthermore, this engagement reflects the normative foundations of Indonesia’s ‘independent and active’ foreign policy and underscores the enduring significance of Asian solidarity rooted in shared experiences of colonial subjugation.